(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: To evaluate treatment results of neonatal hypoxic ischemic encephalopathy (HIE) by applying of therapeutic hypothermia at Camau Obstetrics and Pediatrics Hospital from 2017 to 2022. Method: Cross sectional. 23 HIE newborns were indicated for treatment by therapeutic hypothermia at Camau Obstetrics and Pediatrics Hospital from 2017 to 2022. Results: In 23 HIE newborn, male accounted for 78.3%, severe HIE accounted for 48.8%, the average age at onset of therapeutic hypothermia was 165.0 ± 88.3 minutes; during procedure 56.5% of newborn had convulsions; 26.1% had PH < 7.2; 13.0% had heart rate less 100 beats per min, hyperglycemia requiring insulin-therapy; 8.7% had coagulation disorders, platelets less 100,000 per microliter. The mortality rate accounted for 17.4%; Infants with psychomotor retardation recorded at 12 months old were 20.0%; at 18 months old were 16.7%. Conclusion: Hypothermia is significant in the treatment of moderate-severe HIE, contributing to the reduction of mortality and cerebral sequelae.